Amalan Pematuhan Kelengkapan Pelindung Diri (PPE) Dalam Kalangan Pekerja Di Tapak Bina - Ahmad Latiffi, Aryani; Hazir, Nur Fitrah Hanim; Bilal, Kamalludin (Research in Management of Technology and Business, 2020)
The practice of compliance to Personal Protective Equipment (PPE) at the construction site by workers is very important because it can be said as a rule that must be followed to avoid any risk of accidents. However, among the issues in the construction industry that arise the number of accidents at construction sites is non compliance with the rules of PPE. The objectives of this study are to identify the factors that influence the use of PPE among construction workers and to identify methods to overcome the implementation problem to compliance with the practices of PPE of construction workers. This study used a quantitative approach for gaining data from the Safety and Health Officers recognized by the Department of Occupational Safety and Health (DOSH) in the state of Kedah until year 2019 as respondents. Responses received from 40 respondents by using a set of questionnaire forms. The data gained from the respondents then have been analysed using Microsoft Excel version 2019 to facilitate data processing. The analysis reveals that the highest mean for the first objective of this study is the factor that workers uncomfortable using PPE for a long period have affected the use of PPE. Meanwhile, providing safety induction to the new workers as exposure to safety at the construction site achieves the highest mean for the second objective. In conclusion, the use of PPE is necessary as it is able to prevent the occurrence of injuries and accidents to workers at the construction site.